Improved root turnover assessment using field scanning rhizotrons with branch order analysis. Issue 8 (15th August 2019) - Huo, Changfu; Cheng, Weixin
Abstract: Root turnover is a key process contributing to soil carbon storage, nutrient cycling, and other ecosystem functions. However, quantifying root turnover rates remains highly uncertain and methodologically challenging. Field rhizotrons were employed to quantify root turnover times using median longevities of five branching orders in a Larix gmelinii plantation. Root images were recorded by scanning the rhizotron windows at a monthly interval during four growing seasons. Root demographic data and branching orders were obtained by analyzing these images using Rootfly software coupled with manual mouse‐tracing of individual roots. Root longevities and turnover estimates were calculated using these data. Roots of different branching orders showed significantly different turnover times. The mean turnover times of the first‐order roots and second‐order roots were 284 and 994 d, respectively. Roots of higher branching orders (third to fifth orders) remained alive at the end of the 4‐yr experimental period, indicating much longer turnover times than the duration of the experiment. Root turnover times increased exponentially with branching orders. Further analysis of these data suggested that root branching orders combined with sampling biases, timing of root cohorts, and longevity distribution patterns crucially influenced root turnover times. The method of combining field glass rhizotrons with electronic scanning permits quantification of root turnover for five branching orders in a temperate forest. The overall result empirically demonstrates the crucial role of branching orders for accurately quantifying root turnover times.